Identifying and reducing environmental health risks of chemicals in our society : workshop summary - Pool, Robert; Institute of Medicine (U.S.); Pool, Robert; Rusch, Erin; Institute of Medicine (U.S.). Roundtable on Environmental Health Sciences, Research, and Medicine (National Academies Press, 2014)
"On November 7-8, 2013, the Institute of Medicine's Roundtable on Environmental Health Sciences, Research, and Medicine held a workshop to discuss approaches related to identifying and reducing potential environmental public health risks to new and existing industrial chemicals present in society. Industrial chemicals include chemicals used in industrial processes or commercial products, not including those found in food, pesticides, or pharmaceuticals. Identifying and Reducing Environmental Health Risks of Chemicals in Our Society is a summary and synthesis of the presentations and discussions that took place during the two days of the workshop. The workshop examined successes and areas for improvement within current regulatory programs for assessing industrial chemical safety, frameworks for chemical prioritization to inform targeted testing and risk management strategies, concepts of sustainability and green chemistry that support the design and use of safer alternatives, and efforts to reduce the risk of chemicals in our society."--Publisher's description.
Keywords: Hazardous wastes : Environmental aspects; Hazardous wastes : Risk assessment; United States